Liver metastasis from a non-recurrent atypical cranial meningioma: a case report - Limarzi, Francesco; Solaini, Leonardo; Ercolani, Giorgio; Foschini, Maria Pia; Saragoni, Luca (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Extracranial metastases from atypical meningioma are rare, and even more so in the liver. We report a case of a 68-years-old patient with atypical meningioma, treated with partial surgical resection in 2012, and gamma knife radiotherapy in 2014 in another hospital, exhibiting a liver metastasis 6 years after the initial surgical resection.